Fecundity and reproductive output of the speckled swimming crab Arenacus cribrarius (Lamarck, 1818) (Brachyura, Portunidae) - Pinheiro, MAA; Terceiro, OSL (Brill Academic Publishers, 2000)
Areanaeus cribrarius females were collected over a 12-month period with otter-trawl nets in the Ubatuba littoral zone, Brazil. Ovigerous individuals were measured (CW = carapace width excluding lateral spines) and weighed (WW = wet weight). Each egg brood was weighed (WE = wet weight), dried, and the number of eggs (EN) counted. Scatterplots from EN/CW, EN/WW, and EN/WE were submitted to regression analyses. Mean relative fecundity ((F) over bar') was calculated in each month/season to assess seasonal variation of reproductive intensity. The number of eggs showed a positive correlation with CW, WW, and WE. Fecundity of A. cribrarius ranged from 135,210 to 682,156 eggs, intermediate in comparison with other portunids. Fecundity in Portunidae is typically high; lower values are found in Polybiinae and higher ones in Portuninae. Mean fecundity did not reveal significant differences over months and seasons, but reproductive activity tended to be more intense in summer and winter, a phenomenon related to reduced temperature oscillations as found in subtropical regions.